Synergistic Interactions Between Warming and Elevated Atmospheric CO 2 Increase Soil Organic Carbon Sequestration - Ruiqi Yao; Yike Zhang; Wolfgang Wanek; Zhongkui Luo; Haoran Fu; Scott X. Chang; Cesar Terrer; Mingkai Jiang; Tida Ge; Guopeng Liang; Yuanhe Yang; Yiqi Luo; et al. (Global Change Biology, 2026)
Warming and elevated CO 2 (eCO 2 ) are two potentially opposing climate‐carbon (C) feedback mechanisms that modulate the magnitude of the land C sink, with warming decreasing and eCO 2 increasing C sequestration. However, their net effect on soil organic C (SOC)—the largest terrestrial C stock—remains uncertain. Here, we quantify how warming, eCO 2 , and their interactions influence SOC by using 5558 paired observations from 1392 global studies across ecosystem types. Our study shows that warming reduces SOC by 8.0%, primarily by suppressing aboveground C inputs (−1.0%) and decreasing microbial C use efficiency (−9.9%). Concurrent warming and eCO 2 increase SOC by 7.6%—a synergistic effect larger than eCO 2 alone (+4.8%), primarily contributed by croplands. This outcome may result from increases in plant C inputs and soil nitrogen availability under eCO 2 , which facilitate microbial C assimilation and necromass formation (+3.9%). These processes promote the accumulation of mineral‐associated C (+9.9%) and offset the negative effects of warming. The combined effect of warming and eCO 2 is projected to increase SOC by 27.4 Pg C by 2100. Our findings highlight that synergistic interaction between warming and eCO 2 increases SOC sequestration and enhances SOC stability under future climate change.

Global evidence for joint effects of multiple natural and anthropogenic drivers on soil nitrogen cycling - Yong Zhang; Xiaoli Cheng; Cesar Terrer; Woo‐Jung Choi; Ji Chen; Yiqi Luo; Philippe Ciais (Global Change Biology, 2024)
Global soil nitrogen (N) cycling remains poorly understood due to its complex driving mechanisms. Here, we present a comprehensive analysis of global soil δ 15 N, a stable isotopic signature indicative of the N input–output balance, using a machine‐learning approach on 10,676 observations from 2670 sites. Our findings reveal prevalent joint effects of climatic conditions, plant N‐use strategies, soil properties, and other natural and anthropogenic forcings on global soil δ 15 N. The joint effects of multiple drivers govern the latitudinal distribution of soil δ 15 N, with more rapid N cycling at lower latitudes than at higher latitudes. In contrast to previous climate‐focused models, our data‐driven model more accurately simulates spatial changes in global soil δ 15 N, highlighting the need to consider the joint effects of multiple drivers to estimate the Earth's N budget. These insights contribute to the reconciliation of discordances among empirical, theoretical, and modeling studies on soil N cycling, as well as sustainable N management.

Shifts in soil ammonia‐oxidizing community maintain the nitrogen stimulation of nitrification across climatic conditions - Yong Zhang; Xiaoli Cheng; Kees Jan van Groenigen; Pablo García‐Palacios; Junji Cao; Xunhua Zheng; Yiqi Luo; Bruce A. Hungate; Cesar Terrer; Klaus Butterbach‐Bahl; Jørgen Eivind Olesen; Ji Chen (Global Change Biology, 2024)
Anthropogenic nitrogen (N) loading alters soil ammonia‐oxidizing archaea (AOA) and bacteria (AOB) abundances, likely leading to substantial changes in soil nitrification. However, the factors and mechanisms determining the responses of soil AOA:AOB and nitrification to N loading are still unclear, making it difficult to predict future changes in soil nitrification. Herein, we synthesize 68 field studies around the world to evaluate the impacts of N loading on soil ammonia oxidizers and nitrification. Across a wide range of biotic and abiotic factors, climate is the most important driver of the responses of AOA:AOB to N loading. Climate does not directly affect the N‐stimulation of nitrification, but does so via climate‐related shifts in AOA:AOB. Specifically, climate modulates the responses of AOA:AOB to N loading by affecting soil pH, N‐availability and moisture. AOB play a dominant role in affecting nitrification in dry climates, while the impacts from AOA can exceed AOB in humid climates. Together, these results suggest that climate‐related shifts in soil ammonia‐oxidizing community maintain the N‐stimulation of nitrification, highlighting the importance of microbial community composition in mediating the responses of the soil N cycle to N loading.